Application of precision medicine to the treatment of anaphylaxis. Issue 3 (June 2018) - Labella, Marina; Garcia-Neuer, Marlene; Castells, Mariana
Abstract : Purpose of review: Recognize the presentation of anaphylaxis for prompt management and treatment and to provide tools for the diagnosis of the underlying cause(s) and set up a long-term treatment to prevent recurrence of anaphylaxis. Recent findings: The recent description of phenotypes provides new insight and understanding into the mechanisms and causes of anaphylaxis through a better understanding of endotypes and biomarkers for broad clinical use. Summary: Anaphylaxis is the most severe hypersensitivity reaction and can lead to death. Epinephrine is the first-line treatment of anaphylaxis and it is life-saving. Patients with first-line therapy-induced anaphylaxis are candidates for desensitization to increase their quality of life and life expectancy. Desensitization is a breakthrough novel treatment for patients with anaphylaxis in need of first-line therapy, including chemotherapy, mAbs, aspirin and others. Ultrarush with venom immunotherapy should be considered in patients who present with life-threatening anaphylaxis after Hymenoptera sting with evidence of IgE-mediated mechanisms. Food desensitization is currently being expanded to provide increased safety to adults and children with food-induced anaphylaxis.